The Effect of Meditation on Comprehension of Statements About One-Self and Others: A Pilot ERP and Behavioral Study - Savostyanov, Alexander; Tamozhnikov, Sergey; Bocharov, Andrey; Saprygin, Alexander; Matushkin, Yuriy; Lashin, Sergey; Kolpakova, Galina; Sudobin, Klimenty; Knyazev, Gennady (Frontiers in Human Neuroscience, 2020)
The main goal of this study was to examine the effect of long-term meditation practice on behavioural indicators and ERP peak characteristics during an error-recognition task, where participants were presented with emotionally negative (evoking anxiety or aggression) written sentences describing self-related or non-self-related emotional state and personality traits. In total, 200 sentences written in Russian with varying emotional colouring were presented during the task, with half of the sentences containing a grammatical error that the participants were asked to identify. The EEG was recorded in age-matched control individuals (n=17) and two groups of Samatha meditators with relatively short- (3-5 years’ experience, n=18) and long-term (10-30 years’ experience, n=18) practice experience. Task performance time (TPT) and accuracy of error detection (AED) were chosen as behavioural values. Amplitude, time latency and cortical distribution of P300 and P600 peaks of ERP were used as a value of speech-related brain activity. All statistical effects of meditation were estimated controlling for age and sex. No behavioural differences between two groups of meditators were found. General TPT was shorter for both groups of meditators compared to the control group. Non-meditators reacted significantly slower to sentences about aggression than to sentences about anxiety or non-emotional sentences, whereas no significance was found between meditator groups. Non-meditators had better AED for the sentences about one-self than the sentences about other people, whereas the meditators didn’t show significant difference either. The amplitude of P300 peak in frontal and left temporal scalp regions was higher for long-term meditators in comparison with both intermediate and control groups. The latency of P300 and P600 in left frontal and temporal regions positively correlated with TPT, whereas the amplitude of P300 in these regions had a negative correlation with TPT. We demonstrate that long-term meditation practice increases the ability of an individual to process negative emotional stimuli. The differences in behavioural reactions after onset of negative information that was self-related and non-self-related, which is typical for non-meditators, disappeared due to the influence of meditation. ERP results could be interpreted as a value of increase in voluntary control over emotional state during meditational practice.